Tìm nguyên hàm của hàm số \(f(x)=x\mathrm{e}^x\).
\(\displaystyle\int f(x)\mathrm{\,d}x=(x+1)\mathrm{e}^x+C\) | |
\(\displaystyle\int f(x)\mathrm{\,d}x=(x-1)\mathrm{e}^x+C\) | |
\(\displaystyle\int f(x)\mathrm{\,d}x=x\mathrm{e}^x+C\) | |
\(\displaystyle\int f(x)\mathrm{\,d}x=x^2\mathrm{e}^x+C\) |
Chọn phương án B.
Đặt \(\begin{cases}
u=x\\ v'=\mathrm{e}^x
\end{cases}\Leftrightarrow\begin{cases}
u'=1\\ v=\mathrm{e}^x.
\end{cases}\)
Khi đó $$\begin{aligned}
\displaystyle\int x\mathrm{e}^x\mathrm{\,d}x&=x\mathrm{e}^x-\displaystyle\int\mathrm{e}^x\mathrm{\,d}x\\
&=x\mathrm{e}^x-\mathrm{e}^x+C\\
&=(x-1)\mathrm{e}^x+C.
\end{aligned}$$